Patterns and determinants of antenatal care utilization: analysis of national survey data in seven countdown countries - Ghada Saad-Haddad; Jocelyn DeJong; Nancy Terreri; María Clara Restrepo-Méndez; Jamie Perin; Lara Vaz; Holly Newby; Agbessi Amouzou; Aluísio JD Barros; Jennifer Bryce (Edinburgh University Global Health Society, 2016)
Antenatal care (ANC) is critical for improving maternal and newborn health. WHO recommends that pregnant women complete at least four ANC visits. Countdown and other global monitoring efforts track the proportions of women who receive one or more visits by a skilled provider (ANC1+) and four or more visits by any provider (ANC4+). This study investigates patterns of drop-off in use between ANC1+ and ANC4+, and explores inequalities in women's use of ANC services. It also identifies determinants of utilization and describes countries' ANC-related policies, and programs.